Le rôle des facteurs internationaux dans la législation des petites entreprises en Hongrie - Pilisi, Paul (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
In Hungary, the Party Politburo decided as of January 1st, 1982, to legalize independent small business organizations. International factors with internal socio-economic effects contributed to a hastening in the decision-making process in favour of economic pragma-tism, and contrary to ideological principles. The current Hungarian experience constitutes a model for reformist changes proposed by Michael Gorbatchev in the Soviet Union. The socio-political effects of the Hungarian experience appear also in changes to the political culture. These changes, like the appearance of multiple candidates and political pluralism in elections raise the following question : without the reform of the soviet-type political regime, is it possible to reform the socio-economic System ?